2022
DOI: 10.1002/14651858.cd009759.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal photopheresis versus standard treatment for acute graft-versus-host disease after haematopoietic stem cell transplantation in children and adolescents

Abstract: Extracorporeal photopheresis versus standard treatment for acute graft-versus-host disease after haematopoietic stem cell transplantation in children and adolescents. Cochrane Database of Systematic Reviews, 9(9):CD009759.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…77,85,86 One of the direct effects of ECP is the induction of lymphocyte and monocyte apoptosis mediated via photosensitizing agents generating free oxygen radicals upon exposure to UV light, leading to oxidative stress and cell death. 87 Additionally, ECP has been known to play a role in the transition from Th1 to Th2 immune response, as well as increasing the number of Treg. 88 Multiple studies have demonstrated the efficacy of ECP in refractory GvHD after HSCT; however, limited studies have shown the effectiveness of ECP in GvHD after ITx.…”
Section: Extracorporeal Photopheresismentioning
confidence: 99%
See 1 more Smart Citation
“…77,85,86 One of the direct effects of ECP is the induction of lymphocyte and monocyte apoptosis mediated via photosensitizing agents generating free oxygen radicals upon exposure to UV light, leading to oxidative stress and cell death. 87 Additionally, ECP has been known to play a role in the transition from Th1 to Th2 immune response, as well as increasing the number of Treg. 88 Multiple studies have demonstrated the efficacy of ECP in refractory GvHD after HSCT; however, limited studies have shown the effectiveness of ECP in GvHD after ITx.…”
Section: Extracorporeal Photopheresismentioning
confidence: 99%
“…However, based on our center's experience, given the promising data surrounding ruxolitinib in HSCT and case reports in ITx, earlier intervention in SR-GvHD with JAK inhibitors in patients could be considered. [86][87][88] We would also consider the use of rituximab in patients who develop Epstein-Barr viral viremia during their course of treatment. 9 Data available demonstrate variable outcomes to current therapies that target TNF-α, CD20, or T-cell markers impacted by ATG.…”
Section: Lessons Learned From Hsct and Potential For Future Pharmacol...mentioning
confidence: 99%